Connecting the dots: contributions to creative tourism dynamics in Portugal - Cruz, Ana Rita (2019)
The CREATOUR project – an incubator and a multidisciplinary collaborative research initiative – was created in order to develop a network of creative tourism initiatives in four Portuguese regions. This study’s main purpose was to analyse the dynamics observed in the first stage of implementing this network and to understand the relationships and connections established between creative tourism actors operating at a regional and national level. The research also included examining the main goals and challenges these actors face when developing creative tourism activities in small cities and rural areas of Portugal. Stakeholder and social network analyses were used to process the data collected from each of the 20 pilots involved in this stage of the CREATOUR project. The results highlight relationships between various creative tourism pilot programmes and other regional and/or external actors and include an analysis of stakeholders’ expectations regarding the network’s future development.